European agricultural reform and WTO negotiations in parallel mutually impeding or reinforcing processes? - Bettina Rudloff (Stiftung Wissenschaft und Politik (SWP), 2008)
The Common Agricultural Policy (CAP) of the European Union (EU) is today subject to a double pressure: an internal one, arising from the reform debate caused by the CAP's 'Health Check', and an external one, spurred by the ongoing WTO Round. In the past, EU agricultural reforms and WTO negotiations have mutually influenced one another. The present situation is no exception. The question again arises whether and how this influence will come together, and what path the EU will choose in its internal reform and the WTO negotiations
Keywords: 320